Implementation Of The Group Investigation Model To Improve Learning Outcomes Of 6th Grade Students On Islamic Cultural History Material At MI PSM Gedoro - Nur Fatimah Azzahra; Nabila Khoyrun Nisa; Eka Hidayatin (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2024)
Islamic Cultural History lessons at MI PSM Gedoro often face challenges in increasing student engagement due to being perceived as boring. To address this issue, this study applies the "Group Investigation" (GI) learning model, which aims to encourage teamwork, concentration, peer communication, and cognitive development. In the GI model, students work together to complete learning tasks, such as drawing conclusions or communicating their findings. Through GI, students are given the opportunity to actively seek information, discuss, and collaborate with their group members. The selection of the "Group Investigation" learning model for Islamic Cultural History aims to capture students' attention while working on practice questions, train them to think critically, increase their agility, review previously learned material, understand the content more deeply, and build good cooperation among peers. Classroom Action Research (CAR) is used as the research methodology. Results from the first cycle showed that 86.95% of students scored above 75, which increased to 95.65% in the second cycle. This indicates that the "Group Investigation" learning model effectively improves student engagement and learning outcomes.